1988
DOI: 10.1073/pnas.85.8.2805
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine: a chemotactic factor for human monocytes and its potential role in atherogenesis.

Abstract: Native low density lipoprotein (LDL) does not affect monocyte/macrophage motility. On the other hand, oxidatively modified LDL inhibits the motility of resident peritoneal macrophages yet acts as a chemotactic factor for circulating human monocytes. We now show that lysophosphatidylcholine (lyso-PtdCho), which is generated by a phospholipase A2 activity during LDL oxidation, is a potent chemotactic factor for monocytes. It is not chemotactic for neutrophils or for resident macrophages. Platelet-activating fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
346
3
5

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(365 citation statements)
references
References 42 publications
(32 reference statements)
11
346
3
5
Order By: Relevance
“…A synthetic lysophosphatidyl choline, 1-palmitoyl-lysophosphatidyl choline, had comparable chemotactic activity with an optimum concentration at 25 txM [3,4]. Our experiments demonstrate that HNE is a strong chemoattractant for human monocytes at concentrations which can be found in oxidised LDL.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A synthetic lysophosphatidyl choline, 1-palmitoyl-lysophosphatidyl choline, had comparable chemotactic activity with an optimum concentration at 25 txM [3,4]. Our experiments demonstrate that HNE is a strong chemoattractant for human monocytes at concentrations which can be found in oxidised LDL.…”
Section: Discussionmentioning
confidence: 76%
“…Quinn and co-workers have shown that oxidised LDL induces chemotaxis in human monocytes, with lysophosphatidyl choline being one of its active components [3,4]. Further, oxidised LDL has been shown to be toxic for a variety of cell types including smooth muscle cells, fibroblasts [5] and more recently mouse peritoneal macrophages [6,7], the macrophage-like cell line P388D1 [8] and human monocyte-macrophages [9].…”
Section: Introductionmentioning
confidence: 99%
“…Lysophosphatidylcholine, a product of the PLA,-catalyzed hydrolysis of phospholipids, has been shown to be cytolytic and fusogenic (30). More recently, it has also been reported to be chemotactic for monocytes (31). Thus, uncontrolled activity of the resident PLA, in the cartilage matrix could have quite detrimental effects on the resident cells.…”
Section: Discussionmentioning
confidence: 99%
“…89,90 LPC has been shown to both increase production of proinflammatory cytokines, 69 and have anti-inflammatory effects such as inhibiting high-mobility group protein B1 (HMGB1) secretion(16 h post-treatment with LPC). 91 These effects are dependent on different receptors as well as cell types, but not yet fully understood.…”
Section: Steps Involved In Clearancementioning
confidence: 99%